Acids 'generally recognized as safe' affect morphology and biocompatibility of electrospun chitosan/polyethylene oxide nanofibers. (1st July 2019) - Stie, Mai Bay; Jones, Megan; Sørensen, Henning Osholm; Jacobsen, Jette; Chronakis, Ioannis S.; Nielsen, Hanne Mørck
Highlights: Electrospun chitosan nanofibers produced by use of minute amounts of GRAS acid. Nanofiber morphology and disintegration depend on the type of GRAS acid used. Residual acid is present in fibers after electrospinning, except for acetic acid. Compatibility with cell monolayers relates to residual acid, but not a pH effect. Abstract: Electrospinning of neat chitosan is currently achieved by using strong acids or organic solvents, which limits the use of chitosan nanofibers as biocompatible scaffolds for drug delivery and tissue engineering. The aim was to elucidate the effect of specific acids generally recognized as safe (GRAS) on the properties of electrospun chitosan-based nanofibers. Electrospinning chitosan in dilute acetic acid or succinic acid with polyethylene oxide resulted in white and separated nanofibers, whereas nanofibers electrospun in dilute citric acid were transparent and interconnected. Including succinic or citric acid in the spinning process induced disintegration of the fiber mat after four hours in water, and a concentration-dependent effect on epithelial cell viability. Chitosan nanofibers electrospun in acetic acid maintained their shape and fibrous structure after four hours in water, and showed no effect on cell viability. This study demonstrates that the choice of GRAS acid highly determines the properties of electrospun chitosan nanofibers.